2005
DOI: 10.1299/jsmeb.48.417
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Transport Properties of Ar Thermal Plasmas with Polymer Ablated Vapors and Influence of Their Inclusions on Plasma Temperature

Abstract: Thermodynamic and transport properties of Ar thermal plasmas with polymer ablated vapors at atmospheric pressure were calculated in temperature range up to 30 000 K on the assumption of thermal equilibrium condition. The polymers such as POM (polyoxymethylene), PE (polyethylene) and PMMA (polymethlmethacrylate) are being used in low-voltage circuit breakers or load-break switches as an insulation material and a wall material of arc quenching chamber. These polymers are ablated into the arc plasma during the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Among the four polymers, PMMA vapor produced the best cooling effect on the thermal plasma; specifically, it was found that a strong cooling effect was produced by an equivalent increase of the specific heat due to ionization of the polymer vapor at temperatures of 1000 to 2000 K [12,13]. On the other hand, as explained above, plasma cooling has little direct dependence on the heat required for melting and ablation.…”
Section: Effect Of Thermal Properties Of Ablated Vapor and Solid Polymentioning
confidence: 91%
“…Among the four polymers, PMMA vapor produced the best cooling effect on the thermal plasma; specifically, it was found that a strong cooling effect was produced by an equivalent increase of the specific heat due to ionization of the polymer vapor at temperatures of 1000 to 2000 K [12,13]. On the other hand, as explained above, plasma cooling has little direct dependence on the heat required for melting and ablation.…”
Section: Effect Of Thermal Properties Of Ablated Vapor and Solid Polymentioning
confidence: 91%
“…Then we calculated the thermodynamic and transport properties by applying the first-order Chapman-Enskog approximation to the calculated properties, combined with a set of data on collision cross-sections and the sum of internal states for the respective particles [14]. This analytical model requires the above properties for the POM and PTFE vapors produced by the polymer materials, and for the air that initially fills the computational space.…”
Section: Thermodynamic and Transport Properties Of Polymer Ablation Vmentioning
confidence: 99%
“…These transport properties were obtained by the first order approximation of ChapmanEnskog method [59]. Detailed method for calculation of collision integral had been reported earlier by the co-author Tanaka et al [60,61]. The expressions for various transport parameters are given as follows:…”
Section: Calculation Of Transport Propertiesmentioning
confidence: 99%